Amateur Boxing and Dementia: Cognitive Impairment Within the 35-Year Caerphilly Cohort Study. Issue 3 (15th May 2022) - Gallacher, John; Pickering, Janet; Bayer, Anthony; Heslop, Luke; Morgan, Gareth; Watkins, Angela; Martin, Rhodri; Elwood, Peter
Abstract : Objective: To examine the long-term effects of amateur boxing in a representative population sample of men. Design: The sample was examined every 5 years for 35 years. Cognition was assessed repeatedly from the third examination. Previous boxing experience and dementia were assessed at the fifth examination, and dementia assessed subsequently through medical records. Setting and Assessment of Rick Factors: The Caerphilly Prospective Study investigates risk factors for a range of chronic diseases of diseases. These include life style and behavior, together with biological factors relevant to vascular disease. Participants: 1123 adult men aged 45 to 59 years at baseline, followed for 35 years. Main Outcome Measures: Cognitive impairment. Results: A report by a subject of having boxed "seriously" when younger was associated with a 2-fold increase in cognitive impairment [odds ratio (OR) = 2.27; 95% confidence intervals = 1.18-4.38]. For amnestic (Alzheimer-like) impairment, this rises to OR = 2.78 (95% confidence limits 1.37–5.65). Having boxed is associated with an "advancement" in the onset of the dementia (4.8 years; 95% confidence limits 0.9-8.8 years). Conclusions: Amateur boxing is associated with an increased risk and an earlier onset of cognitive impairment and dementia.